Mapping arealisation of the visual cortex of non-primate species: lessons for development and evolution - Homman-Ludiye, Jihane; Bourne, James A. (Frontiers in Neural Circuits, 2014)
The integration of the visual stimulus takes place at the level of the neocortex, organized in anatomically distinct and functionally unique areas. Primates, including humans, are heavily dependent on vision, with approximately 50% of their neocortical surface dedicated to visual processing and possess many more visual areas than any other mammal, making them the model of choice to study visual cortical arealisation. However, in order to identify the mechanisms responsible for patterning the developing neocortex, specifying area identity as well as elucidate events that have enabled the evolution of the complex primate visual cortex, it is essential to gain access to the cortical maps of alternative species. To this end, species including the mouse have driven the identification of cellular markers, which possess an area-specific expression profile, the development of new tools to label connections and technological advance in imaging techniques enabling monitoring of cortical activity in a behaving animal. In this review we present non-primate species that have contributed to elucidating the evolution and development of the visual cortex. We describe the current understanding of the mechanisms supporting the establishment of areal borders during development, mainly gained in the mouse thanks to the availability of genetically modified lines but also the limitations of the mouse model and the need for alternate species.